2018
DOI: 10.1186/s40510-018-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of dental arch forms in Italian population

Abstract: BackgroundThe aim of this study was the comparison of male and female upper and lower dental arch form in untreated Italian patients by 3D analysis, to find differences in shape, in transversal and longitudinal diameters between sexes, and to give a representative set of population’s dental arch to clinicians in order to provide suitable orthodontic treatment.MethodsThe sample consisted of 3D scans of dental casts deriving from 104 Italian untreated patients (Male = 35, Female = 69) in permanent dentition. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
(30 reference statements)
3
12
1
2
Order By: Relevance
“…Regarding the dental arch height, this study showed that UTAH and UAAH did not change significantly with age over the two-year period. In contrast, previous studies [21] have shown that the height of the arch decreases with age. In clinical practice, for patients with high palates, we do not recommend performing maxillary expansion immediately.…”
Section: Discussioncontrasting
confidence: 78%
“…Regarding the dental arch height, this study showed that UTAH and UAAH did not change significantly with age over the two-year period. In contrast, previous studies [21] have shown that the height of the arch decreases with age. In clinical practice, for patients with high palates, we do not recommend performing maxillary expansion immediately.…”
Section: Discussioncontrasting
confidence: 78%
“…Dental arch forms have been evaluated in different populations [ 14 17 ]. However, no studies have been conducted in Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…This may be related to the difference in the ethnic group, sample size and selection with regard to the facial type. Oliva et al 13 explained that difference by the more ovoid and flatter maxillary arch form of females.…”
Section: Discussionmentioning
confidence: 99%